2018
DOI: 10.1016/j.autrev.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Nature versus nurture in the spectrum of rheumatic diseases: Classification of spondyloarthritis as autoimmune or autoinflammatory

Abstract: Spondyloarthritides (SpA) include inflammatory joint diseases with various clinical phenotypes that may also include the axial skeleton and/or entheses. SpA include psoriatic arthritis, reactive arthritis, enteropathic arthritis and ankylosing spondylitis; the latter is frequently associated with extra-articular manifestations, such as uveitis, psoriasis, and inflammatory bowel disease. SpA are associated with the HLA-B27 allele and recognize T cells as key pathogenetic players. In contrast to other rheumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 123 publications
1
28
0
3
Order By: Relevance
“…Spondyloarthritis, characterized by inflammation of the spine and peripheral joints, includes a range of diseases such as axial spondyloarthritis (axSpA), psoriatic arthritis, reactive arthritis and enteropathic arthritis. 1,2 AxSpA is a chronic inflammatory disease with a heterogeneous clinical phenotype that primarily affects the sacroiliac joints and spine. It represents a spectrum of disease, including ankylosing spondylitis (AS, also known as radiographic axSpA) and nonradiographic axial spondyloarthritis (nr-axSpA).…”
Section: Introductionmentioning
confidence: 99%
“…Spondyloarthritis, characterized by inflammation of the spine and peripheral joints, includes a range of diseases such as axial spondyloarthritis (axSpA), psoriatic arthritis, reactive arthritis and enteropathic arthritis. 1,2 AxSpA is a chronic inflammatory disease with a heterogeneous clinical phenotype that primarily affects the sacroiliac joints and spine. It represents a spectrum of disease, including ankylosing spondylitis (AS, also known as radiographic axSpA) and nonradiographic axial spondyloarthritis (nr-axSpA).…”
Section: Introductionmentioning
confidence: 99%
“…Early long-lasting anti-inflammatory therapy may slow the progression of this irreversible structural damage [4]. This disease has certain autoinflammatory features and is mediated by interactions between innate and adaptive immune cells and cytokines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…SpA is generally considered clinically to be a seronegative disease, due to the paucity of RA‐associated autoantibodies and lack of success identifying prevalent and specific autoantibodies in this patient population. While this may suggest that SpA patients do not mount efficient autoreactive humoral responses or that this disease is autoinflammatory in nature, autoantibodies to β2 microglobulin, protein phosphatase magnesium‐dependent 1A (PPMA1), CD74, LL37, and others have been found in SpA, most commonly in single‐cohort studies (reviewed in Liu et al) . Antibodies to β2 microglobulin were among the first to be described and were found in 68% of ankylosing spondylitis patients in a single study, but were not specific for the disease when compared to patients with lupus or RA .…”
Section: Serologymentioning
confidence: 99%
“…While this may suggest that SpA patients do not mount efficient autoreactive humoral responses or that this disease is autoinflammatory in nature, autoantibodies to β2 microglobulin, protein phosphatase magnesium-dependent 1A (PPMA1), CD74, LL37, and others have been found in SpA, most commonly in single-cohort studies (reviewed in Liu et al 101 ). [102][103][104] Antibodies to β2 microglobulin were among the first to be described and were found in 68% of ankylosing spondylitis patients in a single study, but were not specific for the disease when compared to patients with lupus or RA. 103 Anti-PPMA1 antibodies have also only been described in a single study, but were found to be 67% sensitive and 73% specific for SpA, compared to other forms of IA, and a decrease in the level of these antibodies was…”
Section: Spa Autoantibodiesmentioning
confidence: 99%